Banned books - Heyworth-Dunne, Victoria (DK Publishing, 2022)
"Explores why some of the world's . . . literary classics and seminal non-fiction titles were once deemed too controversial for the public to read--whether for challenging racial or sexual norms, satirizing public figures, or simply being deemed unfit for young readers. From the banning of All Quiet on the Western Front and the repeated suppression of On the Origin of Species, to the uproar provoked by Lady Chatterley's Lover, entries offer a . . . chronological account of censorship, and the . . . role that some banned books have played in changing history"--Provided by publisher.